Seismic-hazard maps for Alaska and the Aleutian Islands - Geological Survey (U.S.) (Geological Survey (U.S.), 1999)
Albers equal-area conic proj., standard parallels 55?N and 65?N, central meridian 160°W (W 170°--W 130°/N 72°--N 50°).; 8 maps on 2 sheets.; Spectral response acceleration shown as contours.; Sheet 1. 10% probability of exceedance in 50 years for peak horizontal acceleration and horizontal spectral response acceleration for 0.2, 0.3, and 1.0 second periods (5% of critical damping) -- Sheet 2. 2% probability of exceedance in 50 years for peak horizontal acceleration and horizontal spectral response acceleration for 0.2, 0.3, and 1.0 second period (5% of critical damping). This archival material has been provided for educational purposes. Ball State University Libraries recognizes that some historic items may include offensive content. Our statement regarding objectionable content is available at: https://dmr.bsu.edu/digital/about